Public Planning in the Entrepreneurial City – The Bo01, Malmö, and Brunnshög, Lund, in Sweden - Madureira, Ana Mafalda (AESOP, 2012)
The paper examines how entrepreneurial urban governance reshapes the role of public planning in Sweden. Entrepreneurial City approaches, driven by municipalities, aim to promote economic development and place attractiveness through branding, marketing, and urban design. Using case studies of Bo01 in Malmö and Brunnshög in Lund, the research analyses how public planning interacts with fragmented stakeholders, financial incentives, and political legitimacy. While business-oriented strategies appear to dominate, public authorities remain crucial as initiators of projects and providers of legitimacy. The study concludes that public planning is adapting to decentralised and market-driven governance but continues to play a decisive role in shaping urban development under neoliberal pressures.
Book of proceedings : AESOP 26th Annual Congress 11-15 July 2012 METU, Ankara
Keywords: Entrepreneurial city; Urban governance; Public planning; Urban renewal; Malmö; Lund; Neoliberalism